Prarancangan Pabrik Asetaldehida dengan Proses Dehidrogenasi Etanol Kapasitas 35.000 Ton/Tahun - Arjiani, Siti Khomariyah; , Ir.Herry Purnama, M.T., Ph.D; , Ir.Haryanto, AR, M.S (2016)
The manufacturer of acetaldehyde with ethanol dehydrogenation process with capacity of 35.000 tons per year was planned to be established in the Industry Area of Gresik, East Java. This plant was planned to produce acetaldehyde with impurity 99%. The procces to make acetaldehyde in gas phase with operation condition are 260-290 º C and 1,25 atm for the pressure, and catalyst used was Cr2Cu2O5. Reactor that used was fixed bed multitube with condition non isothermal and non adiabatic. The reaction is endothermic so it requires heating dowtherm A. Raw materials is ethanol as much as 4.893,6228 kg/hr. for production process needed water as much as 144.888,5623 kg/hr, and the power needed as much as 287,4674 kW. Fixed capital needed is about IDR 563.716.143.239,2530 and working capital is about IDR 123.237.462.510,5700, based from economic analys, profit before taxes is about IDR 225.402.381.651,7860 per year and profit after taxes is about IDR 157.781.667.156,2500 per year. Precent Return On Investment (ROI) before taxes is 39,99% and after taxes is 27,99%. Pay Out Time (POT) before taxes is 2,00 year and after taxes is 2,63 year. Break Event Point (BEP) is 46,85% and Shut Down Point (SDP) is 27,03%. Discounted Cash Flow (DCF) is 35,90%. Based on the economic analys, it can be concluded that this manufacturer is reasonable and establish.